P176 COPD-Related Bronchiectasis; A Real Clinical Entity with Impact on Disease Course and Outcomes. (19th November 2012) - Baker, EH; Kumar, N; Lai, D; Sansom, B; Nair, A; Vlahos, I
Abstract : Introduction and Objectives: Non-CF bronchiectasis is defined as 'symptoms of persistent or recurrent bronchial sepsis related to irreversibly damaged and dilated bronchi' [BTS guidelines 2010]. Radiographic evidence of 'damaged and dilated bronchi' can be seen on CT Thorax in up to 50% of COPD patients. However the contribution of radiographic bronchiectasis to the clinical course of COPD is not fully understood. We aimed to determine the impact of bronchiectasis on lung function, sputum microbiology and outcomes in COPD patients, independent of coexisting emphysema and bronchial wall thickening (BWT). Methods: COPD patients admitted with first exacerbation 1998–2008 were identified retrospectively using ICD10 codes J44.0, 1, 8, 9. Patients with high resolution CT images within 2 years of admission were included. CT scans were graded by consensus of 2 senior thoracic radiologists for severity of bronchiectasis, emphysema and BWT on a 5 point scale (0-absent, 1-minor, 2-mild, 3-moderate, 4-severe). Operational definitions were set prior to scan review and radiologists were blinded to clinical parameters. Results: 406 patients (71±11years, 56% male, FEV1 52±23% predicted) were included. 278 (69%) patients had bronchiectasis: minor, 112 (40%); mild, 81 (29%); moderate, 62 (22%); severe 23 (8%). There was considerable overlap between bronchiectasis and other pathologies (figure ). Bronchiectasis severity correlated with severity of BWT (r=0.276, p<0.001) and emphysema (r=0.120, p=0.015). After adjustment for severity of emphysema and BWT, increasing severity bronchiectasis was not an independent predictor of lung function parameters, but independently determined isolation of Pseudomonas aeruginosa (Odds ratio (OR) 1.39 (95% CI 1.07–1.80), p=0.013) and atypical mycobacteria from sputum cultures (OR 2.44 (95% CI 1.04–5.69), p=0.040). After correction for increasing severity emphysema, BWT, age, gender and comorbidities, increasing severity bronchiectasis determined annual admissions (regression coefficient B=0.14 (95% CI 0.00–0.28), p=0.044) and inpatient days (B=2.1 (95% CI 0.8–3.4), p=0.001) for respiratory causes, but did not influence survival from first hospital admission (p=0.257). Conclusions: Radiographic bronchiectasis in COPD patients is associated with increased respiratory infection and hospitalisation, independent of coexisting emphysema and BWT. COPD-related bronchiectasis is therefore a diagnosis with important clinical implications. Further research should determine whether treatment strategies for non-CF bronchiectasis can improve the clinical course of COPD-related bronchiectasis.